The Impact of Globalization on The Moral Values of Students at Smp/Mts Level - Muhammad Munawir; Bahrur Rohim; Ginanjar Wahyudi; Shuxiang Anindya (Yayasan Adra Karima Hubbi, 2023)
The purpose of this study was to determine whether there is an effect of learning motivation and social studies learning facilities either partially or simultaneously on social studies learning achievement. The population of this study were students in class VII A and VII B of MTS NU Belitang 1 Oku Timur, which numbered 56. The variables studied were learning motivation and learning facilities as independent variables and learning achievement as related variables. The data collection method uses direct observation at school. The results of this study indicate 1) there is an effect of learning motivation on learning achievement, 2) there is an influence of learning facilities on learning achievement 3) there is a simultaneous influence of learning motivation and learning facilities on social studies learning achievement.